Hepatosplenomegaly in liver cirrhosis is caused by reactive oxygen species formation, an increase in apoptosis and autophagy, and pronounced autoimmune reactions - Klimova, E. M.; Drozdova, L. A.; Lavinska, O. V.; Bychenko, E. A.; Kot, Y. H.; Kordon, T. I. (Regulatory Mechanisms in Biosystems, 2021)
Various factors of infectious and toxic genesis can lead to the liver cirrhosis, often accompanied by complications such as recurrent bleeding due to portal hypertension against the background of hepatosplenomegaly. Metabolic changes and disturbances in immunoreactivity occur in the liver and spleen. To substantiate the choice of personalized treatment tactics for patients with hepatosplenomegaly, we investigated individual metabolic predictors and immunopathological processes in patients with: liver cirrhosis and hepatitis B (HBV) and/or hepatitis C (HCV) viruses (I group, n = 52); with herpes viruses CMV (cytomegalovirus) and EBV (Epstein-Barr virus) (II group, n = 48), and with splenomegaly and frequent recurrent bleeding associated with hereditary enzymopathies (III group, n = 15). We used the methods of immunoturbidimetry; enzyme immunoassay; light, fluorescence and confocal microscopy. In group I (HBV/HCV), we revealed a decrease in the C4 component; a significant increase in the phagocytic index and phagocytic number, a reduced number of active phagocytes and the digestion index; a decrease in the IL-1β content and an increase in IL-18 and IL-6. In group II (CMV/EBV), we revealed a high activity of the C3 and a low activity of the C4 component against the background of a high level of ROS in neutrophils; the antineutrophil antibodies (ANCA) formation in 85.7% of patients (71.4% –perinuclear antibodies (pANCA) to myeloperoxidase; 14.3% – cytoplasmic antibodies (CANCA) to proteinase 3). Also, in group II, an increased level of pro-inflammatory cytokines IFN-γ, IL-1β, TNF-α, IL-18 and anti-inflammatory IL-6 was detected. Changes in links of immunity in II group led to the formation of autoimmune reactions in 64.7% of patients, which was expressed in the development of a broad range of antinuclear antibodies ANA (11 specificities, including ANA to chromatin and chromatin-associated proteins, to proteins cytoskeleton, enzymes and enzyme complexes). In group III, we revealed a low absorption capacity of neutrophils, a high frequency of antineutrophil antibodies pANCA occurrence and cANCA (in 67.2% of the examined), and low concentration of TNF-α. The developed model of the stepwise change of immunological markers makes it possible to substantiate the choice of a complex targeted treatment, including antiviral and immunotropic therapy.